2021
DOI: 10.1186/s42779-021-00097-1
|View full text |Cite
|
Sign up to set email alerts
|

The traditional and medicinal use of African breadfruit (Treculia africana Decne): an underutilized ethnic food of the Ibo tribe of South East, Nigeria

Abstract: African breadfruit is an underutilized food security crop which is a delicacy for the Ibo ethnic group of South East Nigeria. It is commonly found in West and Central Africa. It is an evergreen large tree that bears about 20–30 pods containing edible seeds, annually. The edible seeds are used as specialty dishes by the Ibo tribe of South East Nigeria. African breadfruit meals have high dietetic value. The pods, leaves and roots are use in traditional medicine. The leaves are particularly rich in carbohydrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The African breadfruit (Treculia africana Decne) is large evergreen tree found in tropical and sub-tropical humid forests. It is widely distributed in West and Central Africa (Ojimelukwe and Ugwuona, 2021). It belongs to the mulberry family moraceae (Fosberg, 1978;Morton, 1946).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The African breadfruit (Treculia africana Decne) is large evergreen tree found in tropical and sub-tropical humid forests. It is widely distributed in West and Central Africa (Ojimelukwe and Ugwuona, 2021). It belongs to the mulberry family moraceae (Fosberg, 1978;Morton, 1946).…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the mulberry family moraceae (Fosberg, 1978;Morton, 1946). Crude extracts from diferent parts of the plant are used either singly or in combination with other herbs to treat various diseases (Ojimelukwe and Ugwuona, 2021). African breadfruit seeds are highly nutritious and constitute a relatively cheap source of vitamins, minerals, proteins, carbohydrates and fats.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of African breadfruit is usually cooked and eaten as porridge; fried or roasted and eaten as a snack [15]. Ojimelukwe and Ugwuona [16] also stated that seeds of African breadfruit is consumed after it has been mixed with cereals (rice, sorghum and maize) or tubers (yams and shredded cassava). It can as well be used to prepare some food products.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are prepared in various forms such as: boiling, roasting, frying, boiling and pounding, processed into non-alcoholic beverage, starch or flour. They are consumed as snack, side dish (decanted juice) or porridge (22,23). Microorganisms such as: Bacillus subtilis, Erwinia sp., Micrococcus sp., Streptococcus sp., Staphylococcus aureus; Lactobacillus plantarum; Laeuconostoc esenteroides; Aspergillus niger and Rhizopus stolonifer have been reported to be associated with the deterioration and fermentation of African breadfruit (22,24,25,18).…”
Section: Introductionmentioning
confidence: 99%
“…They are consumed as snack, side dish (decanted juice) or porridge (22,23). Microorganisms such as: Bacillus subtilis, Erwinia sp., Micrococcus sp., Streptococcus sp., Staphylococcus aureus; Lactobacillus plantarum; Laeuconostoc esenteroides; Aspergillus niger and Rhizopus stolonifer have been reported to be associated with the deterioration and fermentation of African breadfruit (22,24,25,18). A number of studies have shown that supplementing cereals with legumes or tubers with vegetables and food sources from animals tends to be nutritionally superior and better supported growth and development rather than the single diets of cereal meals (26).…”
Section: Introductionmentioning
confidence: 99%